W obronie „utraconego” logosu - Uniłowski, Krzysztof (Śląskie Studia Polonistyczne, 2014)
In the review of a book Mesjański logos Europy. Mariana Zdziechowskiego i Stanisława Brzozowskiego dyskursy o kulturze Zachodu (Częstochowa, 2012) by Artur Żywiołek, the author presents the monograph as a dissertation in the trend of post-secular thought. The idea of messianism is crucial here (in connection with essayist works of Marian Zdziechowski), as well as the “messianic” category, used to describe texts by Stanisław Brzozowski. In the case of Brzozowski, “messianism” does not describe an idea stance, but turns out to be a mood of critical thought, aimed at overcoming modernity. The author believes that introducing the messianic category is the monograph’s advantage, but also points to paradoxes in the attitude of Artur Żywiołek, who clearly favored these intellectual pursuits within a widely understood modernity, which revalued the community category, the sense-making logos, and sought a way to metaphysically establish the historical experience.